Asociación entre hipotiroidismo y diabetes mellitus en pacientes atendidos en el Hospital Belén de Trujillo - Caro Salazar, Milagritos Brenda Mercedes (2020)
Diabetes mellitus, as well as hypothyroidism, are two pathologies that develop dyslipidemias by themselves and that increase cardiovascular risk. Furthermore, undiagnosed hypothyroidism can alter metabolic control in patients with type 2 diabetes mellitus and amplify the risk of existing cardiovascular disease. It has been determined through different studies that the prevalence of hypothyroidism in diabetic patients is approximately 12 to 13%. Objective: To demonstrate whether there is an association between hypothyroidism and diabetes mellitus in patients treated at the Hospital Belén de Trujillo. Material and Methods: It is a design that is analytical, observational, sectional, cross-sectional. The population will be divided into 2 groups: with or without a diagnosis of diabetes mellitus. The presence of hypothyroidism in each of them will be analyzed. Analysis of the association by calculating the odds ratio (OR).